2011
DOI: 10.1242/dev.056093
|View full text |Cite
|
Sign up to set email alerts
|

Her9 represses neurogenic fate downstream of Tbx1 and retinoic acid signaling in the inner ear

Abstract: SUMMARYProper spatial control of neurogenesis in the inner ear ensures the precise innervation of mechanotransducing cells and the propagation of auditory and equilibrium stimuli to the brain. Members of the Hairy and enhancer of split (Hes) gene family regulate neurogenesis by inhibiting neuronal differentiation and maintaining neural stem cell pools in non-neurogenic zones. Remarkably, their role in the spatial control of neurogenesis in the ear is unknown. In this study, we identify her9, a zebrafish orthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 99 publications
2
77
0
Order By: Relevance
“…High RA levels appear to specify posterior otic development (in particular Tbx1 expression), and low levels are required for anterior gene expression (including markers of neurogenesis) (Bok et al, 2011). A similar positive regulation of otic tbx1 expression by RA (and negative regulation of neurogenesis) has recently been reported in the zebrafish, although mirror image duplications were not observed (Radosevic et al, 2011). Manipulation of RA signalling is also known to affect earlier stages of zebrafish otic development, but only indirectly; notably, early RA inhibition delays the onset of hindbrain fgf3 expression, and so interferes with otic induction (Hans and Westerfield, 2007).…”
Section: Hh and Fgf Act On An Initially Symmetrical Otic Placode Withsupporting
confidence: 58%
“…High RA levels appear to specify posterior otic development (in particular Tbx1 expression), and low levels are required for anterior gene expression (including markers of neurogenesis) (Bok et al, 2011). A similar positive regulation of otic tbx1 expression by RA (and negative regulation of neurogenesis) has recently been reported in the zebrafish, although mirror image duplications were not observed (Radosevic et al, 2011). Manipulation of RA signalling is also known to affect earlier stages of zebrafish otic development, but only indirectly; notably, early RA inhibition delays the onset of hindbrain fgf3 expression, and so interferes with otic induction (Hans and Westerfield, 2007).…”
Section: Hh and Fgf Act On An Initially Symmetrical Otic Placode Withsupporting
confidence: 58%
“…2P,T). We also examined T-box 1 (tbx1), which is expressed in the non-neurogenic otic territory during placodal and vesicle stages (Piotrowski et al, 2003;Radosevic et al, 2011). We found that Dlx3b/4b-depleted embryos at the 12-somite stage also show a complete absence of tbx1 compared with control embryos or embryos lacking Neurog1 or Foxi1 activity (Fig.…”
Section: Independent Regulation Of Sensory and Neuronal Lineages By Dmentioning
confidence: 92%
“…Mechanisms other than Notch signaling may, however, determine the neuronal and sensory hair fate in zebrafish ear development since, unlike in the mouse inner ear and zebrafish pLL systems, the neuronal and sensory hair precursors are specified at about the same time in the zebrafish ear (Andermann et al, 2002;Abello and Alsina, 2007;Millimaki et al, 2007;Radosevic et al, 2011). Thus, the regulatory mechanisms in pLL development and mouse ear development may share more similarities than those of zebrafish ear and mouse ear development.…”
Section: Notch-mediated Cell-fate Determination Affects L1 Neuromast mentioning
confidence: 99%